Possible Hypoxia Signaling Induced Alteration of Glucose Homeostasis in Rats Exposed to Chronic Intermittent Hypoxia - Role of Antioxidant (Vitamin C) and Ca2+ Channel Blocker (Cilnidipine) - K. Das, Kusal; R. Nemagouda, Santosh; G. Patil, Satish; Saha, Sikha (Current Signal Transduction Therapy, 2016)
Background: Hyperglycemia is found to be a regulator of HIF-1α gene expression but the regulation of HIF-1α on glucose homeostasis is unclear. Objective: To determine whether chronic intermittent hypoxia (CIH) alters glucose regulation and such alterations can revert through treatments with either antioxidant (vitamin c) or calcium channel blocker (cilnidipine) in male albino rats. Methods: The rats were divided into six groups i.e. normoxia (21% oxygen), CIH (10% oxygen with cycle time 3:1.5; 8h/day), normoxia with vitamin c (50 mg /100g. b.wt, orally), CIH with vitamin c, normoxia with cilnidipine (1 mg/kg/day; ip) and CIH with cilnidipine. Serum MDA, HIF-1α, fasting plasma glucose, insulin, GTT, HOMA-IR and insulinogenic index were evaluated. Results: Serum HIF-1α and MDA concentration in rats exposed to CIH increased significantly whereas simultaneous CIH with vitamin c and CIH with cilnidipine treatment show reversion of both serum HIF- 1α and MDA concentrations towards normoxic status. CIH rats showed increased fasting glucose level with unchanged plasma insulin level but both vitamin c and cilnidipine treatment improved the status. Elevated HOMA-IR and insulinogenic index along with impaired GTT were found in CIH groups although vitamin c and cilnidipine improved the glucose homeostasis in CIH exposed rats. Conclusion: CIH induces over production of reactive oxygen species as well as hyper activities of sympathetic N-type Ca2+ channels possibly through HIF 1-α expression and influence on insulin signaling by causing hyperglycemia, glucose intolerance and insulin resistance in rats. Simultaneous treatment with vitamin c or cilnidipine improves glucose homeostasis in CIH exposed rats.
Keywords: Chronic intermittent hypoxia